Analysis of Motions in Comic Book Cover Art: Using Pictorial Metaphors. Issue 1 (12th April 2016) - Juricevic, Igor; Horvath, Alicia J.
Abstract : Motion can be depicted using literal pictorial devices (representing features present in the real world) and metaphorical pictorial devices (representing features that do not occur in the real world). How are literal and metaphorical pictorial devices used in comic book cover art? We analyzed the pictorial devices used to depict the motion running in 400 Silver Age (1956–1971) and Bronze Age (c. 1970–1985) superhero comic book covers (Frankenhoff & Thompson, 2012 ). Literal devices (such as arm and leg positions) were used additively; that is, artists preferred to use many literal devices. On the other hand, metaphorical devices (such as action lines) were not used additively; artists preferred to use only one metaphorical device. We propose the Literal Additive Metaphorical One-And-Done (LA-MOAD) theory to account for the use of literal and metaphorical devices in comic book cover art. The differential use of literal and metaphorical devices by comic book artists may be unique to comic book cover art, or it may reflect a basic function of our visual system.